The country study for Japan's official development assistance to the Republic of the Philippines - Japan International Cooperation Agency (Tokyo, Japan Japan International Cooperation Agency, 1999)
This report is based on the discussions and findings of the Committee on the Third Country Study for Japan's Official Development Assistance to the Republic of the Philippines organized by the Japan International Cooperation Agency.
Fi-16640g, Fi-16073g, Fi-16074g, Fi-16075g, Fi-16076g, Fi-16573g donated by Prof. Mamoru Tsuda.
Keywords: Economic assistance, Japanese -- Philippines